Recreational park in state of Pahang / Anuar Ismail - Ismail, Anuar (2003)
Recreational park is an area where the both flora and fauna in the forest has been preserved. It's also to be an area for water catchments, agriculture, environment stability, minimization of damage water and forest. This place is to be main asset in the eco - tourism of Pahang. In other word, eco - tourism have contributed successfully into the Pahang economic and then it known at around the world. The both flora and fauna have been made more tourists attracted come to visit Malaysia as well as state of Pahang. At the same time, it has invited researchers from abroad come in our country to make research and then learn about forest ecosystem in Malaysia. Nowadays, forested area in Pahang has decreased because there is many-forested area had intruded for development. To protect this area, Forest management nowadays must be more efficient and upgraded. Its also to unsure the both flora and fauna have been protected not damage and then will be originate until future generation.